Реалізація протоколу IPSec у різних операційних системах для побудови захищених віртуальних мереж - Корнієнко, Б.Я.; Худяков, О.Ю. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
In the article the main features of the implementation of the protocol ІPSec in different operating systems to create secure virtual networks (Vіrtual Prіvate Network), analyzed their advantages and disadvantages.